2016
DOI: 10.1097/pts.0000000000000313
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students Raising Concerns

Abstract: After a number of high-profile incidents and national reports, it has become clear that all health professionals and all medical students must be able to raise concerns about a colleague's behavior if this behavior puts patients, colleagues, or themselves at risk. Detailed evidence from medical students about their confidence to raise concerns is limited, together with examples of barriers, which impair their ability to do so. We describe a questionnaire survey of medical students in a single-center, examining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…They did, however, appear to feel more comfortable articulating these concerns if the suggestions were constructive or if there was a perceived risk of serious consequences if not addressed. This finding was similar to that of Druce et al, who reported that students were more confident reporting issues regarding patient safety 2 . In our study, dental students considered their own obligation to the team's operation and the patient's well‐being paramount when deciding whether or not to verbalize concerns to the team.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…They did, however, appear to feel more comfortable articulating these concerns if the suggestions were constructive or if there was a perceived risk of serious consequences if not addressed. This finding was similar to that of Druce et al, who reported that students were more confident reporting issues regarding patient safety 2 . In our study, dental students considered their own obligation to the team's operation and the patient's well‐being paramount when deciding whether or not to verbalize concerns to the team.…”
Section: Discussionsupporting
confidence: 89%
“…Dental professionals abide by specific ethical obligations, including the obligation to promote patient welfare, communicate truthfully, and respect the trust between dentist and patient 1 . Many believe that it is a medical professional's duty to report concerns that could put a patient or colleague's well‐being in danger 2 4 …”
mentioning
confidence: 99%
See 3 more Smart Citations